The age-related gliosis and accompanying deficit in spatial learning are unaffected by dimebon (2013)
A non-selective antihistamine, dimebon, has recently emerged as a potential treatment for Alzheimer’s disease and Huntington’s disease. Dimebon exerts several effects in addition to its anti-histaminergic effect, and of particular interest is its ability to enhance cognitive function in several models. The mechanism underlying this is unknown though it has been suggested that it may be associated with its anti-cholinergic action. Dimebon has also been reported to be neuroprotective, perhaps as a result of its ability to stabilize mitochondria. We considered that these effects might impact on the well-described age-related impairment in spatial learning and therefore examined the effect of repeated administration of dimebon on performance of young and aged animals in the Morris water maze. Whereas a clear age-related deficit was observed, dimebon failed to exert any effect on performance. Similarly, dimebon exerted no effect on the age-related increase in hippocampal expression of several markers of microglial and astroglial activation. We conclude that, despite its cognitive enhancing effects in some models, dimebon failed to modulate the deficit in spatial learning in aged rats and the evidence suggests that the drug does not possess anti-inflammatory properties.